WORKING BEAUTIFULLY: DESIGN IS FAILING TO FULLY LIVE UP TO ITS IDEALS. COULD RESTORING ITS LONG‐LOST EMBRACE OF BEAUTY HELP?. (20th November 2020) - Hendricks, Nathan
Abstract : Plato famously considered the three foundational human values to be truth, goodness, and beauty. He further asserted that the absence of one disqualified the others.